Cross sections for formation of 139mCe radioisotope through the 140Ce (n, 2n) reaction over 13.73–14.77 MeV neutrons. (April 2019) - Bharud, Vishal D.; Attar, F.M.D.; Dahiwale, S.S.; Dhole, S.D.; Bhoraskar, V.N.
Abstract: Cross sections for the formation of metastable state of 139 Ce through 14 0 Ce(n, 2n) 139m Ce reaction were measured at five neutron energies over 13.73–14.77 MeV range using the activation method and off-line gamma-ray spectrometric technique. These cross sections were in agreement with the corresponding theoretical cross sections estimated over 10–20 MeV neutrons by EMPIRE-3.2 code, using LEVEDEN 4 and strength function GSTRFN 0 parameters, and TALYS-1.8 code using ldmodel 5 and preeqmode 4 parameters. The estimated most probable excitation energies of 139 Ce were 1.320–3.877 MeV, respectively over 13.73 MeV and 14.77 MeV neutron energies. Highlights: Fast neutron induced (n, 2n) reaction cross sections of rare earth isotope 140 Ce for the formation of 139m Ce, were measured. The neutron energies used were 14.77, 14.68, 14.42, 14.07 and 13.73 MeV neutron energies. The experimental cross sections were measured relative to 27 Al(n, p) 27 Mg reaction. Cross sections estimated by EMPIRE-3.2 and TALYS-1.8 codes are in good agreement with the experimental cross sections.